Efficacy of Nebulized 3% Hypertonic Saline in the Management of Bronchiolitis in Children Less Than 2 Years of Age - Jan, Abdullah; Tariq, Asfand; Alyas, Mian Ahmad; Riaz, Lubna; Bano, Shehar; Bibi, Perveen (Biological and Clinical Sciences Research Journal, 2025)
Bronchiolitis is a major cause of hospitalization among infants and young children, particularly in developing countries like Pakistan. Despite advances in supportive care, optimal management strategies remain under evaluation. Nebulized 3% hypertonic saline (HS) has been proposed as a safe and effective therapy that improves mucociliary clearance, reduces airway edema, and accelerates recovery. Objectives: This randomized controlled trial aimed to evaluate the efficacy of nebulized 3% HS compared with 0.9% normal saline (NS) in children aged < 2 years with bronchiolitis. Methods: This single-center randomized controlled trial was conducted at the Department of Pediatric Medicine, Shaikh Zayed Hospital, Lahore, from August 2024 to January 2025. A total of 26 children under two years of age with a first episode of bronchiolitis were enrolled through non-probability consecutive sampling and randomly divided into two equal groups. Group A received nebulized 3% HS with salbutamol and budesonide, while Group B received nebulized 0.9% NS with the same adjuncts. The primary outcome was rapid clinical recovery and discharge within 72 hours; secondary outcomes included changes in the Wang Clinical Severity Score (WCSS) and the duration of hospital stay. Data were analyzed using SPSS v25, with a p-value ≤ 0.05 considered significant. Results: The mean age of participants was 11.2 ± 5.8 months, with equal gender distribution (61.5% male). Baseline WCSS was comparable between groups (7.31 ± 1.02 vs. 7.45 ± 0.97; p = 0.72). Significant improvement was observed in Group A at 60 minutes (p = 0.04), 90 minutes (p = 0.02), 24 hours (p < 0.001), and at discharge (2.71 ± 0.55 vs. 3.86 ± 0.67; p < 0.001). Rapid recovery within 72 hours occurred in 92.3% of Group A versus 53.8% of Group B (p = 0.03). The mean hospital stay was significantly shorter in the HS group (2.6 ± 0.8 days) compared to the NS group (4.1 ± 0.9 days; p < 0.001). Overall treatment efficacy was achieved in 92.3% of the HS group compared with 53.8% in the NS group (p = 0.02). Conclusion: Nebulized 3% hypertonic saline significantly improved clinical severity scores, accelerated recovery, and reduced hospital stay compared to normal saline in children under two years with bronchiolitis. Its use offers a cost-effective, evidence-based intervention that may substantially reduce pediatric morbidity and healthcare burden in resource-limited settings like Pakistan.